(untitled) (Élisée - Revista de Geografia da UEG, 2023)
Agribusiness and mineral production was expanded in the municipality of Quixeré, Ceará-Brazil, aimed at rentier action in the territory, encouraging the territorialization of capital by the installation of national and multinational companies. In Quixeré, there is the territorialization of capital in the countryside with the territorialization of agribusiness and mining companies, anchored by the latifundio and the land concentration. The objective of this work is to reveal aspects of the agrarian question in the municipality, especially when dimensioning the size of the latifundium and evaluating which activity concentrates the most land. It is expected to facilitate the understanding of the local agrarian issue by listing the transformations and vectors that modify the territory, as well as indicating which enterprises are responsible for expanding private land ownership. With the research, it is concluded that the latifundium is a central element in the agrarian question of Quixeré, particularly intensified by the presence of large companies in the countryside.